2007
DOI: 10.1152/ajpcell.00418.2006
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol and dihydrotestosterone regulate endothelial cell barrier function after hypergravity-induced alterations in MAPK activity

Abstract: Postflight orthostatic intolerance (POI) was reported to be higher in female than male astronauts and may result from sex-dependent differences in endothelial cell (EC) barrier permeability. Here the effect of 17beta-estradiol (E(2)) and dihydrotestosterone (DHT) on the expression of the tight junction protein occludin, EC barrier function, and MAPK activation over time was tested after subjecting human umbilical vein EC (HUVEC) to brief hypergravity identical to that experienced by astronauts during liftoff (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Very different stimulation modalities have been used (continuous or discontinuous, g forces ranging from 2 to 2,000×g, treatments ranging from minutes to days). This could be the reason for contrasting results sometimes obtained by the authors on ECs (Spisni et al 2003;Versari et al 2007;Sumanasekera et al 2006Sumanasekera et al , 2007. Till now the studies have been conducted in HUVECs, where prolonged hypergravity exposure results in inhibited cell growth, enhanced migration and increased NO synthesis (Spisni et al 2003;Versari et al 2007).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Very different stimulation modalities have been used (continuous or discontinuous, g forces ranging from 2 to 2,000×g, treatments ranging from minutes to days). This could be the reason for contrasting results sometimes obtained by the authors on ECs (Spisni et al 2003;Versari et al 2007;Sumanasekera et al 2006Sumanasekera et al , 2007. Till now the studies have been conducted in HUVECs, where prolonged hypergravity exposure results in inhibited cell growth, enhanced migration and increased NO synthesis (Spisni et al 2003;Versari et al 2007).…”
Section: Discussionmentioning
confidence: 95%
“…Till now the studies have been conducted in HUVECs, where prolonged hypergravity exposure results in inhibited cell growth, enhanced migration and increased NO synthesis (Spisni et al 2003;Versari et al 2007). Others have documented a reduced barrier function and increased permeability after brief hypergravity profile (Sumanasekera et al 2006(Sumanasekera et al , 2007. This fact, together with the consideration that in physiological conditions endothelial cells bear different mechanical stimuli depending on the vascular district, suggested us the hypothesis that cell response to gravitational stress could be different in micro-and macrocirculation.…”
Section: Discussionmentioning
confidence: 99%
“…One could speculate that excess androgens in adult males and females may have differential effects on the endothelium, which may contribute to the differences in the endothelial pathways affected. Indeed, sexrelated differences with respect to both endothelial signaling molecule expression and endothelium-dependent vascular function have been documented [51][52][53][54]. The contribution of T, if any, to the differential and sex-specific vascular endothelial function in the prenatal T-exposed adults warrants future investigation.…”
Section: Androgens In Sex-specific Endothelial Dysfunctionmentioning
confidence: 99%
“…They also showed that hypogravity stimulated endothelial growth, enhanced nitric oxide production, and altered actin distribution [29]. Sumanasekera et al reported that brief hypergravity decreased the barrier function, which was attributed to the inhibition of MAPK phosphorylation, in HUVECs [26,27].…”
Section: Introductionmentioning
confidence: 97%